Dialogue Between Catholics and Muslims at Wolosambi Parish Based on Church Teaching’s - Raga, Polikarpus; Hadia, Herlina; Riyanto, Fransiskus Armada (Journal of Asian Orientation in Theology, 2025)
This study focuses on the dialogical experiences of Catholics in the Saint Johan Baptizt Wolosambi Parish with Muslims. Catholics have a positive view and attitude toward Muslims. Dialogue is closely linked to the lived testimony in daily experiences. The Catholic Church, through various documents, especially since the Second Vatican Council and beyond, recognizes the need for dialogue with other religions. Several studies have examined Church documents and their relevance to the praxis of interreligious dialogue. This research describes the relational experience between Catholics and Muslims in Wolosambi Parish. This relational experience is connected to Church documents on interreligious dialogue. The authors collected data through observations and in-depth interviews with Catholics and Muslims in the area.